Design and testing of a novel peptide vaccine against the mucosal pathogen moraxella catarrhalis with emphasis on protecting chronic obstructive pulmonary disease patients from exacerbations - Gehad Mohsen Yassin; Ahmed Sherif Attia; Magdy Ali Amin (Cairo : Gehad Mohsen Yassin, 2016)
Moraxella catarrhalis is an established pathogen that is causing substantial infections to both children and adults. However, so far there is not effective vaccine that could halt the spread of these infections. Immunoinformatics tools were used to predict M. catarrhalis epitopes that would be capable of offering immunoprotection among major proportions of human populations worldwide. Mice were immunized with best three peptides then challenged with M. catarrhalis in the pulmonary clearance model. Finally, antibodies against these epitopes were detected in humans. Immunoinformatics analyses identified 44 epitopes which are predicted to be good MHC II binders and at the same time show high population coverages worldwide. Upon intraprotenial mice immunization with the best three peptides, peptide 2A3 derived from the lactoferrin binding protein A showed superior activity in immunogenicity and in clearing M. catarrhalis from mice lungs. Higher clearance was obtained upon combining intraprotenial with intranasal immunization. Upon examining the sera from otitis media children infected with M. catarrhalis, antibodies levels against peptide 2A3 were significantly higher than those detected in non otitis media ones. Peptide 2A3 is the first promising peptide based vaccine against M. catarrhalis. Immunoinformatics predicts it should have a global protection around the world.
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Microbiology and Immunology
Issued also as CD
Keywords: Exacerbations; Mucosal pathogen moraxella; Novel peptide vaccine against